Determinants of Self Medication Practice among Adolescents of Higher Secondary Schools, Bhaktapur - Prajapati, Laxmiswori; Ranjit, Uma Devi (Journal of Nursing Education of Nepal, 2023)
Introduction: Self-medicationis an important health issue globally and more common in developing  countries like Nepal and India. Self-medication is one of the common and preferred modes resorted  by adolescents.  Method: A descriptive cross sectional study was carried out to find out the determinants of self medication practice among adolescents, data was collected among 426 adolescents of grade 11 and  12 enrolled in five higher secondary schools, Bhaktapur municipality by using structured and semi structured self-administered questionnaire. Proportionate stratified sampling technique was used to  select the schools with, enumeration sampling technique.  Results: Data analysis was done by using descriptive and inferential statistics. Multivariate Logistic  regression analysis was used to identify the determinants of self-medication practice. Out of 426  adolescents, 69.71% had used self-medication. The bivariate analysis showed number of factors  associated with self-medications such as age, gender, type of family, educational level of respondent  and parents, occupation of parents, income source and family income status. The multivariate analysis  showed that probability of consuming drugs increase in adolescent with illiterate mother 1.901 times  more likely to use self-medication than those literate mothers and whose family income status was  poor 1.59 times more likely to use self-medication. Conclusion: The study concluded that educational level and family income status were the determinants  for self-medication among adolescents of higher secondary school of Bhaktapur.
Keywords: Adolescents; Determinants; Self–Medication